Comparative study of multimode CYTOP graded index and single-mode silica fibre Bragg grating array for the mode shape capturing of a free-free metal beam - Theodosiou, Antreas; Polis, Michael; Lacraz, Amédéé; Kalli, Kyriacos; Komodromos, Michael; Stassis, Andreas (My University, 2016)
The work described in this paper involved two different material fibre Bragg grating (FBG) arrays, investigating their performance as quasi-distributed sensors by capturing the vibrating response of a free-free metal beam close to its resonance frequencies. A six meter length of low-loss, gradient-index, multimode CYTOP fibre and of SMF-28 were used for the inscription of multiple FBG sensors using a femtosecond laser inscription method. The FBG arrays were multiplexed in the wavelength domain using a high-speed commercial demodulator, from which we recovered wavelengthand time-dependent displacement information. We compared the vibration response of the two arrays and using a novel computation algorithm we extract the first mode shape of the free-free metal beam that was exited at its first resonance frequency using a vibrating force.
Keywords: FBG array; Femtosecond laser; Polymer optical fibres; Shape sensing; Surface displacement sampling